Voices of Resilience - O’Connor, Pam. author. aut Link
XXII, 229 p.
Keywords: This book presents the results of a study that examined the multiple layers of stigma and discrimination experienced by women infected and affected by HIV/AIDS in a low socio-economic area of Mumbai, India. Using exploratory qualitative methods and underpinned by the psychosocial framework and gendered perspectives the study attempts to represent the voicesof affected and infected women. The book first focuses on a global overview of HIV,presents data on the Indian context and provides a synthesis of HIV in relation to stigma, discrimination and gender. The second part of the book probes the depth of impact on women’s lives using the lenses of gender, economic status, the environment and physical health. The framework was further modified and extended to include threats revealed by and strengths indentified in infected and affected women. The analysis revealed that strategies to address stigma and discrimination need to address the social, cultural, religious and systemic barriers to changing attitudes. The book portrays the resilience of each woman’s spirit and the unique capacity of the women to cope, to find strength, to pursue life and to maintain hope when their dreams and the dreams of their children have been shattered through HIV/AIDS.